One-dimensional dispersion in trickling filter in the case of rhombic arrangement - Ünlu, A; Sekerdag, N (Selper Ltd, Publications Div, 2000)
This paper deals with the dispersion phenomena of conservative tracer materials. Rhombic arrangements are taken into account in trickling filters and a non-uniform flow condition is maintained. A general differential equation is derived and applied to describe the flow over a spherical-jet chain. A computer program aided solution method is presented. The calculation of the dispersion coefficients by using this dispersed flow model approach is shown by examples for different now rate conditions through trickling filters.
Keywords: trickling filter; rhombic arrangement; dispersion